'A Fanatical Reverence for Gandhi': Nationalism and Police Militancy in Bengal during the Non-cooperation Movement. Issue 6 (2nd November 2017) - Silvestri, Michael
ABSTRACT: Police militancy and strike actions featured prominently throughout the British Empire in the years after the First World War. While the demands of police for greater pay and better conditions of service were rooted in economic circumstances, police in diverse locales also forged tentative alliances with labour and trade union movements, sparking government fears of police 'Bolshevism'. In the Indian province of Bengal, Indian police officers took a more radical stance and expressed widespread sympathy with the non-cooperation campaign of Mohandas Gandhi and its goal of swaraj or independence. Police discussed Gandhian teachings, threatened strike actions and formed the first association of non-European policemen in India, the Bengal Police Association. While ultimately the police remained loyal to the British Raj, the events in Bengal demonstrate the continuing links of colonial policemen to social, economic and political currents within the societies in which they operated, the force of nationalism in Bengal during the noncooperation movement and the strategies used by the colonial state to maintain police loyalty. An interrogation of Bengal police support for Gandhi not only complicates our portrait of the policemen who upheld the raj, but also sheds light on a significant moment in the 'modernisation' and professionalisation of colonial police forces and the tensions between their role in upholding colonial authority and their relationship to emerging labour and nationalist movements.